PELAKSANAAN URUSAN PEMERINTAHAN BIDANG PENGENDALIAN PENDUDUK DAN KELUARAGA BERENCANA OLEH DP3AP2KB PROVINSI RIAU DAN PERWAKILAN BKKBN PROVINSI RIAU TAHUN 2021 - Donni Nuryadi; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Government affairs in the field of population control and family planning are included in concurrent non-basic service affairs. They are divided into authorities between the central government and local governments based on Law Number 23 of 2014 about Regional Government. The representatives of the Riau Province BKKBN from the Central Government and the Office of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) Riau Province is the Regional Apparatus Organizations (ODP). This is a government agency that carries out government affairs in the field of population control and family planning in Riau Province level within the framework of regional autonomy. This study uses a descriptive qualitative method which aims to determine the implementation of government affairs in the field of population control and family planning by the government in Riau Province in 2021. The results of this study are that the implementation of government affairs in the field of population control and family planning has not been carried out optimally by the government in Riau Province in 2021. The existence of the representatives of the central government at the provincial level who carry out government affairs in the field of population control and family planning has an impact on the weakening of the role of the Provincial Government in carrying out the same jobs. The presence of the Riau Province BKKBN as the representative of the central government in handling population control and family planning in Riau Province is the impact of the absence of a BKKBD in Riau Province. In addition, there are still representatives of the central government who carry out population control and family planning matters even though there is already regional autonomy. It is because of the low commitment of the Riau Provincial Government to fully implement government affairs in the field of population control and family planning, which is a priority program in the Riau Province. Keywords: Government Affairs, Government Institutions, Population Control and Family Planning